Analisis Peran Desentralisasi sebagai Solusi untuk Mengatasi Ketimpangan Pembangunan di daerah - Septiyandri Sya'bani Zidane; Desi Mehliyana; Davina Indah Ramadhani; Muhammad Rizki; Muhammad Rusdan; Syalsabila Syalsabila; Citra Darminto (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The development disparity among regions in Indonesia poses a significant challenge that can hinder economic growth and create social jealousy. This study aims to analyze the factors causing development disparity, the role of decentralization in addressing it, and the forms of decentralization implementation in Indonesia. The study collects data on variations in the Human Development Index (HDI) using a qualitative method and a descriptive analytical methodology. infrastructure distribution, and development fund allocation. The findings indicate that disparities are caused by differences in natural resources, demographic conditions, concentration of economic activities, and uneven fund allocation. Decentralization through regional autonomy, special allocation funds, special autonomy, and direct regional head elections offers solutions to accelerate equitable development. However, the success of decentralization heavily depends on regional readiness in managing resources and enhancing infrastructure and human resource capacities..